2018
DOI: 10.1101/418053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct observation of individual tubulin dimers binding to growing microtubules

Abstract: The biochemical basis of microtubule growth has remained elusive for over thirty years despite being fundamental for both cell division and associated chemotherapy strategies. Here, we combine interferometric scattering microscopy with recombinant tubulin to monitor individual tubulins binding to and dissociating from growing microtubule tips. We make the first direct, single-molecule measurements of tubulin on-and off-rates. We detect two populations of transient dwell times, and determine via binding-interfa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…[87] These fast rates of single-molecule tubulin dimer kinetics have recently been contested by new measurements using interferometric scattering microscopy with gold nanoparticle-labeled tubulin. [88,89] Here, the authors reported two distinct, albeit slower tubulin off-rates, corresponding to different sites of tubulin association at the microtubule end distinguished by the number of longitudinal and lateral bonds formed. Regardless of the exact rates of tubulin on/off kinetics, the effects of microtubule growth fluctuations are likely to be important for the size of the GTP-cap and overall microtubule stability.…”
Section: Microtubule Growth Fluctuations and Aging Add Complexity To ...mentioning
confidence: 90%
See 1 more Smart Citation
“…[87] These fast rates of single-molecule tubulin dimer kinetics have recently been contested by new measurements using interferometric scattering microscopy with gold nanoparticle-labeled tubulin. [88,89] Here, the authors reported two distinct, albeit slower tubulin off-rates, corresponding to different sites of tubulin association at the microtubule end distinguished by the number of longitudinal and lateral bonds formed. Regardless of the exact rates of tubulin on/off kinetics, the effects of microtubule growth fluctuations are likely to be important for the size of the GTP-cap and overall microtubule stability.…”
Section: Microtubule Growth Fluctuations and Aging Add Complexity To ...mentioning
confidence: 90%
“…Careful examinations using light imaging approaches and improved image analysis techniques have provided recent evidence of dramatic changes in the microtubule end structure over time, including microtubule end tapering, protofilament splitting, and repair (Figure 4), [39,41,73,98,102] as well as allowed measurements of tubulin polymerization kinetics at a single-molecule level. [88,89] Nevertheless, investigation of the microtubule end at the ultra-structural level still requires high-resolution EM approaches.…”
Section: Microtubule Growth Fluctuations and Aging Add Complexity To ...mentioning
confidence: 99%
“…Microtubules with higher protofilament number have a smaller angular separation between protofilaments, and this can affect the strength of lateral tubulin bonds and the ease with which they form. The current understanding of the molecular details of microtubule growth relies on combining experiments with modeling (43)(44)(45)(46)(47)(48). For example, one recent model of microtubule polymerization assumes that growing microtubule tips have flared protofilaments, to the end of which tubulin dimers are added before the protofilaments associate with each other laterally (49).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the nucleotide composition, both kinetics of microtubule assembly and the structure of the growing microtubule end remain areas of intense interest (Kerssemakers et al, 2006) (Schek et al, 2007) (Gardner et al, 2011a) (Mickolajczyk et al, 2019) (Guesdon et al, 2016)(Estévez-Gallego et al, 2020) (Mcintosh et al, 2018) (Atherton et al, 2018) (Gudimchuk et al, 2020). The addition of inherently curved GTP-tubulin dimers to the ends of microtubule protofilaments and their subsequent straightening into closed polymer lattice have been reported to result in a variety of intermediate structures, including disconnected and splayed individual protofilaments (Mcintosh et al, 2018) (Gudimchuk et al, 2020), multi-protofilament sheets (Chrétien et al, 1995) (Guesdon et al, 2016) (Atherton et al, 2018) and overall tapered microtubule ends (Mandelkow et al, 1991) (Reid et al, 2019).…”
Section: Discussionmentioning
confidence: 99%